DESIGN AND ANALYSIS OF DUAL BAND ANTENNA LOADED WITH METAMATERIAL - Dr.K. Vidhya (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the proposed work, a dual band antenna has been designed on different types of substrate for resonating between 2.4GHz and 5.8GHz. The oddity of the proposed work lies in loading Split Ring Resonator (metamaterial) in the ground plane of the antenna for improving the return loss in the higher band and the radiation pattern. Various antenna performance parameters such as Gain, Bandwidth, Return loss and Radiation pattern were investigated with and without meta material loading for different dielectric materials.